PENGENALAN KEAMANAN DIGITAL DAN PEMANFAATAN AI SECARA BIJAK BAGI SISWA-SISWI - Taswanda Taryo; Achmad Hindasyah; Nilovar Asyiah (Abdi Jurnal Publikasi, 2026)
The rapid development of digital technology and Artificial Intelligence (AI) has had a significant impact on daily life, including in the field of education. Students are now able to utilize various AI-based applications to support learning processes, access information quickly, and enhance creativity. However, alongside these positive opportunities, there are risks that cannot be ignored, such as low levels of digital security literacy, vulnerability to cybercrime, and the potential misuse of AI technology. In response to these conditions, this Community Service Program (Pengabdian kepada Masyarakat/PKM) is designed to provide an introduction to digital security and the wise use of AI for students. The activities focus on increasing awareness of the importance of protecting personal data, promoting ethical behavior in digital media usage, and improving understanding of responsible AI utilization. In addition, the program introduces various examples of AI applications that support learning, enabling students to understand both the benefits and risks of AI technology. The implementation methods include interactive material presentations, group discussions, case studies related to digital security, and hands-on practice using simple AI applications. Through this approach, students are expected to more easily understand the concepts presented and apply them in their daily lives.With the implementation of this PKM program, students are expected to develop better digital security literacy as well as the skills to utilize AI wisely, ethically, and productively, thereby becoming better prepared to face the challenges of the digital era.